Holiday as a Phenomenon of Kazakhs: Sociocultural and Historical Aspects - Islambekov, Alibek; Zhiyenbekova, Ainur; Azizov, Aziz; Arymbayeva, Kulimkhan; Alikbayeva, Marzhan (Journal of Posthumanism, 2025)
The article considers the role of holidays in Kazakh culture, their historical development, cultural significance and influence on social and family relations. It analyses traditional holidays, their rites and rituals, as well as their significance in the context of modern Kazakh society. Holidays play a significant role in the life of each nation, reflecting its cultural and historical characteristics. This study examines holidays as a phenomenon of Kazakhs, their meaning, evolution and influence on social life. The study is based on historical and cultural analysis, as well as on modern sociological data. Holidays are an important part of the cultural heritage of any nation. They not only reflect traditions and customs, but also serve as a means of preserving and transmitting cultural values. Kazakhs, like many other peoples, have a unique system of holidays, which is the result of their historical development and socio-cultural changes. In this study, we will focus on analyzing the holidays of Kazakhs, their functions and influence on society.